2022
DOI: 10.3389/fpubh.2022.892042
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Surgical Treatments in Patients With Pure Cervical Radiculopathy

Abstract: BackgroundTraditionally paired meta-analysis revealed inconsistencies in the safety and effectiveness of surgical interventions. We conducted a network meta-analysis to assess various treatments' clinical efficacy and safety for pure cervical radiculopathy.MethodsThe Embase, PubMed, and Cochrane Library databases were searched for randomized controlled trials (RCTs) comparing different treatment options for patients with pure cervical radiculopathy from inception until October 23, 2021. The primary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Cervical radiculopathy (CR), an aging-related disease, typically manifests as neck and shoulder pain, ultimately resulting in atrophy of cervical paraspinal muscles (PSMs). [1] Its epidemiological characteristics have extensively been investigated worldwide, especially since the world is approaching an aging society. Its age-adjusted incidence is 83 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical radiculopathy (CR), an aging-related disease, typically manifests as neck and shoulder pain, ultimately resulting in atrophy of cervical paraspinal muscles (PSMs). [1] Its epidemiological characteristics have extensively been investigated worldwide, especially since the world is approaching an aging society. Its age-adjusted incidence is 83 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…Its age-adjusted incidence is 83 per 100,000 people. [1] Strine and Hootman showed that approximately one-third of the US population is suffering from CR, i.e., neck pain and muscle dysfunction, representing a significant medical and economic burden. [2] A recent meta-analysis, including the subgroup analysis of 1202 individuals, estimated a 2.3% overall prevalence of CR and a 24.2% prevalence of asymptomatic nerve compression, with the elderly population exhibiting a significantly higher prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of surgical approaches and procedures have been described to treat radicular symptoms related to cervical degenerative pathology in patients who are un-responsive to conservative treatment or those with clinical symptoms of myelopathy. [1][2][3][4][5][6] The primary goal of operative treatment in patients with radiculopathy alone is decompression of the cervical nerve root to decrease pain and allow for improvement in sensory or motor deficits. 7 The most common surgical options for treating cervical radiculopathy are anterior cervical discectomy and fusion (ACDF), posterior cervical foraminotomy (PCF), and cervical disk replacement (CDR).…”
mentioning
confidence: 99%
“…A variety of surgical approaches and procedures have been described to treat radicular symptoms related to cervical degenerative pathology in patients who are unresponsive to conservative treatment or those with clinical symptoms of myelopathy 1–6 . The primary goal of operative treatment in patients with radiculopathy alone is decompression of the cervical nerve root to decrease pain and allow for improvement in sensory or motor deficits 7 .…”
mentioning
confidence: 99%